1992
DOI: 10.1210/endo.130.2.1733731
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-alpha alters bovine luteal cell synthetic capacity and viability.

Abstract: Tumor necrosis factor-alpha (TNF-alpha) is a macrophage-derived cytokine that is also reportedly produced by granulosal cells and is localized in luteal cells. The present study employed serum-free culture of midcycle bovine luteal cells to investigate the effects of TNF-alpha, alone and with other cytokines, on luteal function. TNF-alpha (1-1000 ng/ml) produced a dose-dependent increase in prostaglandin (PG)F2 alpha and 6-keto-PGF1 alpha synthesis on all days of culture, but had no effect on basal progesteron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
76
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 33 publications
(2 reference statements)
3
76
1
Order By: Relevance
“…In addition, recent observations suggest that cytokines including tumor necrosis factor-α (TNF-α) released from macrophages may influence the process of functional luteolysis [5]. However, most data on granulosa cells in vitro have described the inhibitory actions of TNF-α on steroidogenesis [6][7][8], while the data on luteal cells in vitro revealed little or no effect of TNF-α [5,9,10] on the progesuring luteolysis, immune cells, especially white blood cell series such as macrophages [1][2][3], D eosinophils [3,4] and T lymphocytes [2], have been observed within the corpus luteum (CL). The major role of the immune cells within the CL at this stage is most likely to be a phagocytosis of the CL terone (P) production.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, recent observations suggest that cytokines including tumor necrosis factor-α (TNF-α) released from macrophages may influence the process of functional luteolysis [5]. However, most data on granulosa cells in vitro have described the inhibitory actions of TNF-α on steroidogenesis [6][7][8], while the data on luteal cells in vitro revealed little or no effect of TNF-α [5,9,10] on the progesuring luteolysis, immune cells, especially white blood cell series such as macrophages [1][2][3], D eosinophils [3,4] and T lymphocytes [2], have been observed within the corpus luteum (CL). The major role of the immune cells within the CL at this stage is most likely to be a phagocytosis of the CL terone (P) production.…”
mentioning
confidence: 99%
“…The major role of the immune cells within the CL at this stage is most likely to be a phagocytosis of the CL terone (P) production. Therefore, the predominant action of cytokines on luteal cells may be to induce the release of prostaglandins (PG) rather than to suppress steroidogenesis [5]. Indeed, we have demonstrated that TNF-α slightly stimulated the release of P and PGF2α from the microenvironment within the CL at the mid-luteal stage when it was applied through a microdialysis system (MDS) that was implanted in the CL in cyclic ewes [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bagavandoss et al have reported that the number of macrophages infiltrating into the corpus luteum increases during luteolysis in rabbits [18,19], and not only PGF2a but also several kinds of cytokines produced by immunocytes play a role as luteolytic factors [18][19][20][21][22]. Tumor necrosis factor (TNF)-o produced by activated macrophages was discovered by Carswell et al [23].…”
mentioning
confidence: 99%
“…Tumor necrosis factor (TNF)-o produced by activated macrophages was discovered by Carswell et al [23]. It has been demonstrated that TNF-a derived from macrophages which infiltrated into the corpus luteum plays a role in luteolysis [19,22]. TNF-a has many biological effects in in vivo and in vitro studies.…”
mentioning
confidence: 99%